The apocryphal epistle to the Laodiceans : an epistolary and rhetorical analysis - Tite, Philip L., 1969- (Texts and Editions for New Testament Study, 2012)
Challenging nearly two centuries of scholarship, this book offers the first close analysis of the apocryphal epistle to the Laodiceans. A near consensus in scholarship has emerged in which Laodiceans is dismissed as a random collection of phrases plucked from the undisputed Pauline letters, which lacks any organizational structure or theological sophistication. In The Apocryphal Epistle to the Laodiceans, Philip Tite offers a detailed analysis of this Latin letter by exploring the epistolary conventions utilized by the letter writer. What emerges is a pseudonymous text that is a carefully crafted paraenetic letter with a discernible rhetorical situation. By highlighting Laodiceans' use of Paul as a literary culture hero, Tite situates the letter within second-century Christian identity formation.